Hybrid AI for estimating water levels at ungauged river locations via graph neural networks and terrain-aware edges - Anh Minh Truong; Guangan Chen; Michiel De Baets; Michiel Vlaminck; Brian Booth; Hiep Luong (Advances in Water Resources, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Design and calibration of a nitrate decision support tool for groundwater wells in Wisconsin, USA - Paul F. Juckem; Nicholas T. Corson-Dosch; Laura A. Schachter; Christopher T. Green; Kelsie M. Ferin; Eric G. Booth; Christopher J. Kucharik; Brian P. Austin; Leon J. Kauffman (Environmental Modelling & Software, 2024)

Chow diet in mouse aging studies: nothing regular about it - Jennifer Lee; Chloe Purello; Sarah L. Booth; Brian Bennett; Christopher D. Wiley; Ron Korstanje (GeroScience, 2023)
Chow diet is used in the majority of rodent studies and, although assumed to be standardized for dietary source and nutritional contents, it varies widely across commercial formulations. Similarly, current approaches to study aging in rodents involve a single-diet formulation across the lifespan and overlook age-specific nutritional requirements, which may have long-term effects on aging processes. Together, these nutrition-based disparities represent major gaps in geroscience research, affecting the interpretation and reproducibility of the studies. This perspective aims to raise awareness on the importance of rodent diet formulation and proposes that geroscientists include detailed descriptions of all experimental diets and feeding protocols. Detailed reporting of diets will enhance rigor and reproducibility of aging rodent studies and lead to more translational outcomes in geroscience research.

Modeling population effects of the Deepwater Horizon oil spill on a long‐lived species - Lori H. Schwacke; Tiago A. Marques; Len Thomas; Cormac G. Booth; Brian C. Balmer; Ashley Barratclough; Kathleen Colegrove; Sylvain De Guise; Lance P. Garrison; Forrest M. Gomez; Jeanine S. Morey; Keith D. Mullin; et al. (Conservation Biology, 2022)
The 2010 Deepwater Horizon (DWH) oil spill exposed common bottlenose dolphins ( Tursiops truncatus ) in Barataria Bay, Louisiana to heavy oiling that caused increased mortality and chronic disease and impaired reproduction in surviving dolphins. We conducted photographic surveys and veterinary assessments in the decade following the spill. We assigned a prognostic score (good, fair, guarded, poor, or grave) for each dolphin to provide a single integrated indicator of overall health, and we examined temporal trends in prognostic scores. We used expert elicitation to quantify the implications of trends for the proportion of the dolphins that would recover within their lifetime. We integrated expert elicitation, along with other new information, in a population dynamics model to predict the effects of observed health trends on demography. We compared the resulting population trajectory with that predicted under baseline (no spill) conditions. Disease conditions persisted and have recently worsened in dolphins that were presumably exposed to DWH oil: 78% of those assessed in 2018 had a guarded, poor, or grave prognosis. Dolphins born after the spill were in better health. We estimated that the population declined by 45% (95% CI 14–74) relative to baseline and will take 35 years (95% CI 18–67) to recover to 95% of baseline numbers. The sum of annual differences between baseline and injured population sizes (i.e., the lost cetacean years) was 30,993 (95% CI 6607–94,148). The population is currently at a minimum point in its recovery trajectory and is vulnerable to emerging threats, including planned ecosystem restoration efforts that are likely to be detrimental to the dolphins’ survival. Our modeling framework demonstrates an approach for integrating different sources and types of data, highlights the utility of expert elicitation for indeterminable input parameters, and emphasizes the importance of considering and monitoring long‐term health of long‐lived species subject to environmental disasters. Article impact statement : Oil spills can have long‐term consequences for the health of long‐lived species; thus, effective restoration and monitoring are needed.

Land O’Lakes Workshop on Microsampling: Enabling Broader Adoption - Enaksha R Wickremsinhe; Qin C. Ji; Carol R. Gleason; Melanie Anderson; Brian P. Booth (The AAPS Journal, 2020)

AAPS Workshop Report on ICH M10 - Brian Booth; Faye Vazvaei; Eric Fluhler; Heather Myler; Eric Woolf (The AAPS Journal, 2020)
Over the last decade, several regulatory guidelines on bioanalytical method validation (BMV) have been issued by regulatory agencies around the world. This has left the bioanalytical community struggling with regional differences in regulatory expectations when preparing for global pharmaceutical submissions. The International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) has the mission to achieve greater harmonization worldwide to ensure that safe, effective, and high-quality medicines are developed and registered in the most resource-efficient manner. Following calls for harmonization, ICH-selected bioanalytical method validation and sample analysis among its topics for guidance development and earlier this year released a draft guideline (M10) on BMV for public consultation. In response, the American Association of Pharmaceutical Scientists (AAPS) held a 3-day workshop to provide a forum for regulatory, industry, and academic scientists to discuss the guideline and hear various points of view on key aspects. While there was agreement that the draft guideline is generally well written and comprehensive, specific topics generated considerable discussion and, in some cases, revision recommendations for consideration by the expert working group (EWG) responsible for the guideline content. This report provides a summary of the workshop proceedings.

The Future of Midlatitude Cyclones - Jennifer L. Catto; Duncan Ackerley; James F. Booth; Adrian J. Champion; Brian A. Colle; Stephan Pfahl; Joaquim G. Pinto; Julian F. Quinting; Christian Seiler (Current Climate Change Reports, 2019)
Purpose of Review This review brings together recent research on the structure, characteristics, dynamics, and impacts of extratropical cyclones in the future. It draws on research using idealized models and complex climate simulations, to evaluate what is known and unknown about these future changes. Recent Findings There are interacting processes that contribute to the uncertainties in future extratropical cyclone changes, e.g., changes in the horizontal and vertical structure of the atmosphere and increasing moisture content due to rising temperatures. Summary While precipitation intensity will most likely increase, along with associated increased latent heating, it is unclear to what extent and for which particular climate conditions this will feedback to increase the intensity of the cyclones. Future research could focus on bridging the gap between idealized models and complex climate models, as well as better understanding of the regional impacts of future changes in extratropical cyclones.

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Time dependent pharmacokinetics of pembrolizumab in patients with solid tumor and its correlation with best overall response - Hongshan Li; Jingyu Yu; Chao Liu; Jiang Liu; Sriram Subramaniam; Hong Zhao; Gideon M. Blumenthal; David C. Turner; Claire Li; Malidi Ahamadi; Rik de Greef; Manash Chatterjee; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Workshop Report: Crystal City VI—Bioanalytical Method Validation for Biomarkers - Mark E. Arnold; Brian Booth; Lindsay King; Chad Ray (The AAPS Journal, 2016)

Validation of an in vitro model of erbB2+ cancer cell redirection - Jang Pyo Park; Walker M. Blanding; Jessica A. Feltracco; Brian W. Booth (In Vitro Cellular & Developmental Biology - Animal, 2015)

A Review of Historical and Future Changes of Extratropical Cyclones and Associated Impacts Along the US East Coast - Brian A. Colle; James F. Booth; Edmund K. M. Chang (Current Climate Change Reports, 2015)

Workshop Report: AAPS Workshop on Method Development, Validation, and Troubleshooting of Ligand-Binding Assays in the Regulated Environment - Marian Kelley; Lauren Stevenson; Michaela Golob; Viswanath Devanarayan; Joao Pedras-Vasconcelos; Roland F. Staack; Rand Jenkins; Brian Booth; Eric Wakshull; Ronald Bowsher; Marie Rock; Sherri Dudal; et al. (The AAPS Journal, 2015)

Workshop Report: Crystal City V—Quantitative Bioanalytical Method Validation and Implementation: The 2013 Revised FDA Guidance - Brian Booth; Mark E. Arnold; Binodh DeSilva; Lakshmi Amaravadi; Sherri Dudal; Eric Fluhler; Boris Gorovits; Sam H. Haidar; John Kadavil; Steve Lowes; Robert Nicholson; Marie Rock; et al. (The AAPS Journal, 2015)

Meeting Report: Metabolites in Safety Testing (MIST) Symposium—Safety Assessment of Human Metabolites: What’s REALLY Necessary to Ascertain Exposure Coverage in Safety Tests? - Hongying Gao; Abigail Jacobs; Ronald E. White; Brian P. Booth; R. Scott Obach (The AAPS Journal, 2013)

The impact of acute strenuous exercise on TLR2, TLR4 and HLA.DR expression on human blood monocytes induced by autologous serum - Stephen Booth; Geraint D. Florida-James; Brian K. McFarlin; Guillaume Spielmann; Daniel P. O’Connor; Richard J. Simpson (European Journal of Applied Physiology, 2010)

Validation of a whole-body cortisol extraction procedure for channel catfish (Ictalurus punctatus) fry - Brian C. Peterson; Natha J. Booth (Fish Physiology and Biochemistry, 2010)

Quantitative Bioanalytical Methods Validation and Implementation: Best Practices for Chromatographic and Ligand Binding Assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (Pharmaceutical Research, 2007)

Workshop/conference report—Quantitative bioanalytical methods validation and implementation: Best practices for chromatographic and ligand binding assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (The AAPS Journal, 2007)

Impact of pharmacometrics on drug approval and labeling decisions: A survey of 42 new drug applications - Venkatesh A. Bhattaram; Brian P. Booth; Roshni P. Ramchandani; B. Nhi Beasley; Yaning Wang; Veneeta Tandon; John Z. Duan; Raman K. Baweja; Patrick J. Marroum; Ramana S. Uppoor; Nam Atiqur Rahman; Chandrahas G. Sahajwalla; et al. (The AAPS Journal, 2005)